2017
DOI: 10.1016/j.buildenv.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort in buildings using radiant vs. all-air systems: A critical literature review

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(75 citation statements)
references
References 42 publications
(59 reference statements)
2
56
0
4
Order By: Relevance
“…Depending on various parameters, a savings potential of 10%‐80% compared to conventional air‐conditioning systems was reported in literature . Furthermore, radiant cooling can result in improved thermal comfort compared to all‐air systems …”
Section: Example Of the Coupling Applicationsmentioning
confidence: 99%
“…Depending on various parameters, a savings potential of 10%‐80% compared to conventional air‐conditioning systems was reported in literature . Furthermore, radiant cooling can result in improved thermal comfort compared to all‐air systems …”
Section: Example Of the Coupling Applicationsmentioning
confidence: 99%
“…This question is important for the application of radiant systems and has been listed as top-ten unsolved question [2]. A review study by Karmann et al [3] indicated that despite many theoretical benefits, such as reduced air movement [4,5], less draft risk [6] and smaller air temperature gradient [7], radiant systems are not more thermally comfortable. Because an increasing number of buildings tend to use radiant heating/cooling systems and with the emergence of new radiant system types [8], the thermal comfort effects of radiant asymmetries should be considered when designing and operating those systems.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review was conducted by Karmann et al [18] in order to assess if radiator systems provide better, equal or lower thermal comfort than all-air systems. Karmann et al [18] concluded that a limited number of studies are available and, therefore, a solid answer cannot be given. Nevertheless, there is suggestive evidence that radiant systems may provide equal or better comfort than all-air systems.…”
Section: Radiatorsmentioning
confidence: 99%